Developing indoor heat-health warning systems for vulnerable populations - Choo-Yoon Yi; Chengzhi Peng (Field Actions Science Reports)
With respect to the changing environmental conditions and extreme heat events associated with climate change, this article presents a review of existing heat-health warning systems* and discusses how such systems can be further augmented to account for indoor environmental conditions. The development of indoor heat-health warning systems is urgently needed to enhance the health and social care for vulnerable populations who spend long hours indoors. As a proof-of-principle study, we first introduce an indoor heat-health warning system developed for the general population in the UK, demonstrating its use case based on the 2013 heatwave event. Focusing on older people living in residential care — one of the most vulnerable populations worldwide — we illustrate the capabilities of an indoor heat-health warning system through a modelling framework which evaluates the impact of climate (change) on a building’s heat and energy performance, from neighbourhood to city scales. An indoor heat-health warning system deployed at care homes should be able to foretell residents’ indoor heat exposures given forecasts of impending heatwave events.*. Heat health warning systems (HHWSs) are weather-(forecast)-based alert system designed to notify decision-makers and the public about upcoming heat events. They provide guidance on preventing heat-related health effects when forecasts predict that temperatures (and/or humidity) will reach or exceed thresholds at which significant health impacts are likely.